Perancangan Slingbag Untuk Kegiatan Street Feeding Komunitas Feed Not Bomb Bandung - Adisti Ratna Delia; Mohamad Arif Waskito (Aliansi Desainer Produk Industri Indonesia (ADPII), 2022)
This research is the process of designing sling bag street feeding activities intended for the Bandung feed not bomb community at the age of 20-25 years. This research is based on the needs and opportunities due to cat overpopulation and the issue of welfare of abandoned animals that occur in Indonesia resulting in the emergence of the movement to care for abandoned animals. Based on data taken in the community feed not bomb Bandung street feeding activities are one of the alternatives that can be done to help the welfare of cats, but when the activity takes place street feeders to have difficulty bringing the needs of street feeding activities. The purpose of this research is to produce a sling bag product design that can organize luggage, make it easier for users, and must have good durability. The resulting design has a novelty value offered, namely sling bag devoted to the use of street feeding activities because there is no special bag to support these activities. The design process is carried out through the design thinking process approach and at the end of the process is produced a prototype design is tested on street feeding activities. Keyword: feed not bomb, cat, community, sling bag, street feeding